Mixibius parvus sp. nov. and Diphascon (Diphascon) ziliense sp. nov., two new species of Eutardigrada from Sicily - Lisi, Oscar; Sabella, Giorgio; Pilato, Giovanni (Zootaxa, 2014)
Two new species, Mixibius parvus sp. nov. and Diphascon (Diphascon) ziliense sp. nov. are described from Sicily. Mixibius parvus sp. nov. has three macroplacoids and a microplacoid and differs from M. tibetanus, the only other known species of the genus with those characteristics, in having a wrinkled cuticle without true small tubercles, a shorter microplacoid, smaller claw pt index values, and in lacking a cuticular bar on the first three pairs of the legs. Diphascon (Diphascon) ziliense sp. nov. lacks eye spots, has a pharyngeal bulb with two macroplacoids and a septulum, and possesses lunules and cuticular bars on the legs. It is similar to D. (D.) ramazzottii and D. (D.) procerum but differs from them in characters of the cuticular ornamentation and, in addition, from D. (D.) ramazzottii in having lunules and slightly longer claws in proportion to the body size and to the buccal tube. The new species differs from D. (D.) procerum in having stouter claws with a wider common portion and with the main branches shorter in proportion to the total length of the respective claws.